2021
DOI: 10.3390/rs13061046
|View full text |Cite
|
Sign up to set email alerts
|

Estimating Processing Tomato Water Consumption, Leaf Area Index, and Height Using Sentinel-2 and VENµS Imagery

Abstract: Crop monitoring throughout the growing season is key for optimized agricultural production. Satellite remote sensing is a useful tool for estimating crop variables, yet continuous high spatial resolution earth observations are often interrupted by clouds. This paper demonstrates overcoming this limitation by combining observations from two public-domain spaceborne optical sensors. Ground measurements were conducted in the Hula Valley, Israel, over four growing seasons to monitor the development of processing t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 57 publications
0
8
1
Order By: Relevance
“…In this study, MTCI, based on Band-5, showed low performance in tomato LAI estimation. MTCI was previously found to have low correlation with tomato crop coefficient (K c ) and height [11]. Nevertheless, MTCI was highly correlated with LAI of cotton and wheat in the present study.…”
Section: Discussioncontrasting
confidence: 67%
See 4 more Smart Citations
“…In this study, MTCI, based on Band-5, showed low performance in tomato LAI estimation. MTCI was previously found to have low correlation with tomato crop coefficient (K c ) and height [11]. Nevertheless, MTCI was highly correlated with LAI of cotton and wheat in the present study.…”
Section: Discussioncontrasting
confidence: 67%
“…Therefore, despite the achievements in estimating LAI using Sentinel-2 bands in tomato, cotton, and wheat, additional measurements of wheat are needed to estimate Sentinel-2 bands saturation levels in that crop. Moreover, owing to the spectral resemblance of the Sentinel-2 MSI and the VENµS sensors [2,11,53], a combination with VENµS might facilitate better agricultural monitoring, considering its high two-day temporal resolution.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations